Nationalism Moh. Hatta through the Sigil Application in History Learning - Sari, Endah Puspita; Agung, Leo; Joebagio, Hermanu (Universitas Sebelas Maret, 2020)
Learning in schools today still uses the method of lectures and the use of Microsoft office power points. The use of teaching materials is still considered less supportive of historical learning in today's schools. Therefore, interesting and effective teaching materials are required, one of which is sigil application. This research aims to encourage the renewal of teaching materials, especially in historical learning. The approach used in this study is a qualitative method. The population used is grade XI students of IPS SMA N 1 Pacitan school year 2019/2020. The type of sample used is simple random sampling technique. Data collection techniques using polls. Based on the results of the study can be concluded: 1) Moh nationalism. Hatta was a nationalism handed over entirely to the people. 2) sigil application is one of the software applications used to create e- books in Epub format. 3) Historical learning using sigil applications can affect students' nationalism.